A perspective on coarse-graining methodologies for biomolecules: resolving self-assembly over extended spatiotemporal scales - Banerjee, Akash; Hooten, Mason; Srouji, Nour; Welch, Rebecca; Shovlin, Joseph; Dutt, Meenakshi (Frontiers in Soft Matter, 2024)
The process of self-assembly of biomolecules underlies the formation of macromolecular assemblies, biomolecular materials and protein folding, and thereby is critical in many disciplines and related applications. This process typically spans numerous spatiotemporal scales and hence, is well suited for scientific interrogation via coarse-grained (CG) models used in conjunction with a suitable computational approach. This perspective provides a discussion on different coarse-graining approaches which have been used to develop CG models that resolve the process of self-assembly of biomolecules.